Bacteria sense the antibiotic rifampicin through a widespread dual-promoter based alarm system - Sudzinová, Petra; Knežová Balgová, Tamara; Schwarz, Marek; Juříková Mikesková, Klára; Hegrová, Karolína; Vítovská, Dragana; Rawat, Priyanka; Bobková, Šárka; Kočárková, Veronika; Natarajan, Saran; Pospíšilová, Debora; Křenková, Alena; et al. (Nucleic acids research, 2026)
Most antibiotics are natural compounds or their derivatives, and bacteria have evolved defensive mechanisms to resist them. Many of these mechanisms are still poorly understood or unknown. This study reveals that in Bacillus subtilis, the transcription factor HelD increases resistance to rifampicin by protecting its target, RNA polymerase (RNAP). This protection is mediated by the HelD N-terminal domain that penetrates into RNAP to the close vicinity of the rifampicin binding pocket. Importantly, the bacterium detects low rifampicin levels using a unique regulatory system involving two convergent promoters with finely tuned kinetic properties. In the absence of rifampicin, the stronger antisense promoter inhibits transcription from the sense promoter. In the presence of subinhibitory rifampicin concentration, the antisense promoter is more likely to encounter rifampicin-bound RNAP. This relieves the repression from the sense promoter, increasing its transcription by almost two orders of magnitude, boosting helD expression. A similar two-promoter arrangement also controls the pps gene, which encodes a rifampicin-modifying enzyme. These findings define a widespread bacterial response system sensitive to rifampicin, as this dual-promoter architecture is conserved across many bacterial species and found upstream of genes potentially involved in rifampicin resistance, such as those for hydrolases, transporters, and transferases.
Keywords: Anti-Bacterial Agents; regulace genové exprese u bakterií; DNA řízené RNA-polymerasy; DNA-Directed RNA Polymerases; bakteriální proteiny; antibakteriální látky; Gene Expression Regulation, Bacterial; Promoter Regions, Genetic; genetická transkripce; Bacillus subtilis; Bacterial Proteins; Transcription, Genetic; Transcription Factors; Rifampin; bakteriální léková rezistence; transkripční faktory; promotorové oblasti (genetika); Drug Resistance, Bacterial; rifampin